The relationship between vegetable intake and chronic gastric disorder among community-dwelling residents aged 35 years and older in China - Guan, Yue; Dong, Yu; Xu, Huiqing; Xu, Yunting; Ao, Guofeng; Ji, Jing; Yuan, Jie; Zhang, Yan; Ye, Qing (Frontiers in Nutrition, 2025)
BackgroundChronic gastric disorder (CGD) is a common disease among people in China. However, very few studies are available on the association between lifestyle factors, such as vegetable consumption, and CGD. This study aimed to investigate the relationship between vegetable intake and CGD among adults in regional China.MethodsIn this cross-sectional survey conducted in 2023, a total of 38,051 community-dwelling residents aged 35 years and older were randomly selected from the Nanjing municipality in China. The outcome event was self-reported CGD, referring to chronic atrophic gastritis (CAG) or chronic gastric ulcer (CGU). The vegetable intake level was assessed using a validated food frequency questionnaire (FFQ) and classified into two subgroups based on the consumption recommendation (≥300 g/day), as advised by the Chinese Nutrition Society (CNS) and tertiles. Logistic regression analyses were performed to compute the odds ratio (OR) and 95% confidence interval (CI) in order to examine the associations between vegetable intake and CGD.ResultsAmong the participants analyzed, the overall prevalence of CGD was 16.6%. Moreover, the proportion of participants who met the vegetable consumption recommendation was 32.0%. After adjusting for potential confounding factors, participants who met the recommended vegetable intake had significantly higher odds of experiencing CGD (OR = 1.16, 95%CI = 1.10, 1.23) compared to those who did not meet the recommendation. Additionally, adults in the high (OR = 1.26, 95%CI = 1.18, 1.35) and middle (OR = 1.16, 95%CI = 1.09, 1.24) tertiles of vegetable intake were also more likely to experience CGD compared to those in the low tertile. Furthermore, the positive associations between vegetable intake (defined by either the recommended level or tertiles) and CGD were consistently observed across subgroups stratified by age, sex, or residential area.ConclusionVegetable intake was found to be positively associated with CGD among community-dwelling residents aged 35 years and older, both overall and across subgroups stratified by age, sex, or residential location in regional China. This study suggests that vegetable intake may be an influencing factor in the prevention of CGD among adults in China. The study also indicates that population-level interventions promoting vegetable consumption could be a viable option for preventing CGD.